Rheum telianum (Polygonaceae), a new species from Southeastern Anatolia (Turkey) - İlçi̇m Ahmet; Karahan, Faruk (Phytotaxa, 2020)
Rheum telianum is described as a new species from Kayatepe village (south-eastern Anatolia, Turkey). It is morphologically related to the west-central Asiatic R. ribes and R. rhizostachyum from which can be easily distinguish by its stem surface (slightly verrucose), leaf number, shape, and size (usually 1-basal leaf or rarely with a small one at base, reniform-rotate, 6.5–100 × 4.5–56 cm), achene shape and size (cordate-triangular, 8–15 × 8–16 mm). The distribution, notes on ecology, and conservation status of the new species are also provided.